Normalising sexualised violence in popular culture: eroding, erasing and controlling women in rock music - Hill, Rosemary Lucy; Richards, Daisy; Savigny, Heather (Feminist Media Studies, 2021)
How does music play a role in normalising men’s sexual violence towards women? Using mainstream rock and metal music as an illustrative case study, we offer a nuanced account of the ways in which men’s sexual violence is normalised. Using a definition of sexual violence drawn from Liz Kelly’s notion of a continuum, which reframes sexual violence as the loss of women’s ability to control sexual experiences, we explore the ways in which sexual violence is a prevalent lyrical and audio-visual component of rock and metal songs. We show that a pernicious theme of rock and metal over the last 25 years is the erosion of women’s ability to refuse sexual activity and to have voice and be heard. We argue that this erosion of women’s consent takes place through the representational use of emotional abuse, controlling/coercive behaviour, and through the objectification of women. The erasure of consent presented through these methods becomes a key means of establishing sexual control. Through manipulation, the confusion of what counts as sexual violence and how it is defined, men’s sexual violence against women is normalised.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2021.1902368
Keywords: Feminism; music video; rock lyrics; rock music; sexual violence